Perfis de espalhamento Raman ressonante em estruturas unidimensionais de carbono: cadeias lineares e nanotubos quiralmente enriquecidos - Luciano de Moura Guimaraes (2011)
In resonant Raman scattering experiments using several laser lines, the intensity profile of the spectra as a function of the laser energy is related to the vibrational and electronic structure of the material. In this work, we have measured and interpreted the resonant Raman profiles for samples of chirality enriched single-walled carbon nanotube and for polyyne types linear carbon chains, confined inside of the single and double walled carbon nanotubes. The results for the chirality enriched samples reveal the resonant Raman behavior of the G band for nanotube with specific (n,m) chirality and show a dispersive discrete profile for the G band, which cannot be observed in results for bundled samples or dispersions containing several chiralities. The resonant Ramanprofile of the G band is well represented by the full quantum-mechanical model based on third order time-dependent perturbation theory considering different lifetimes for the resonant processes with the incident and scattered photons, showing that it is not necessary to consider approximations in the semi-classical model. A comparative study of the resonant profiles of the vibrational modes of linear carbon chains inside of carbon nanotubes showed that there are screening effects on the excitonic states of these molecules due to the nanotube. In addition, changes in the G band of the nanotubes show that thereis charge transfer between the molecule and the nanotube.